Elevating the Community-Based Approach towards River Management: A Case Study of Squatter’s Community in Inanam-Likas River Basin in Sabah, Malaysia - Ramli Dollah; Adi Jafar; Marsitah Mohd Radzi; Nordin Sakke; Mohammad Tahir Mapa; Amrullah Maraining (Faculty of Geography UGM and Indonesian Geographers Association, 2023)
River pollution is one of the major threats to the environment worldwide, especially in developing countries such as Malaysia. Despite numerous actions, policies, and efforts to alleviate river pollution, the issue continues to threaten environmental sustainability. Drawing from the case study of the Inanam-Likas river basin on the western coast of Sabah, Malaysia, this paper advocates for an enhanced and inclusive approach to squatter communities in river management. This paper emphasises the importance of adopting a multistakeholder partnership, aligning with the principles of SDG17 from the Global Partnership for Sustainable Development. It argues that it is essential to recognise squatter communities residing along the riverbanks as key stakeholders, alongside governmental and non-governmental agencies, in the comprehensive management of river ecosystems. This study uses qualitative methods, including field observations, library research, and interviews. A total of 36 participants, including enforcement officers, policy makers, community leaders, and squatter residents, were interviewed to gather insights and information about river management and pollution in this area. Findings from the study reveals that, despite various efforts to address the issue of river pollution in the Inanam-Likas River basin, employing diverse approaches such as enforcement measures, the implementation of waste management technology, and several other strategies, the current initiatives are not proving to be sustainable in effectively managing this complex challenge. The study underscores the need for a more nuanced and sustainable approach that addresses the root causes contributing to river pollution in this area. Hence, this study advocates for a community-based approach to river management policy, facilitated by local authorities and relevant agencies. The absence of support from squatter communities undermines the implementation of effective mitigation strategies and essential policies for river management, thereby presenting a substantial challenge to environmental sustainability due to the persisting threat of river pollution.